(untitled) (Fiep Bulletin - online, 2013)
Introduction and object: The isokinetic dynamometer quantify parameters like torque production , muscular potential, fatigue and several muscular work, that becomes one important tool to highlight and provides objects to trace diagnostics. The Kinesio Tape is an application through a tape that can be stretched without restriction to the mechanism of contraction, dropsy reduction, pain and spasm with high utilization at prevention at e injuries. Therefore, analyzing the behavior of knee extenders muscles with or without functional bandage application. Methods: The sample contained 10 active volunteers, with 21,1 ± 2,1 years, 78,1kg e 1,76m, that was submitted twice to the protocol of isokinetic concentric evaluation of 60°/s to get the PT, compost by 4 steps, called heating, familarisation, evaluation and cooling, with one week of break and evaluations, the first application without functional bandage called Concentric Fase compost for the Concentric Group (GC) and the second application with functional bandage, called Bandage Fase, compost by the Bandage Group (GB). The data were analyzed in a software. BioEstat 5.0, working with normal test Shapiro-Wilk, parametrics values found in this moment used T Student test for analyzes between group GC and GB. Results: Didn’t have differences p=NS, between GC and GB, both at dominant member (MD), both at not dominant member (MÑD). The average of PT and GC to the MD was 213,6 Nm and for MÑD was 212,9 Nm. For the GB group the average of PT was 207,9 Nm and 206,5 Nm to MD and MÑD. Conclusion: Not Observed differences between concentric isokinetic PT of the volunteers quadriceps when was used Functional Bandage. It is suggested for the work realization one big sample and one protocol patronization for better results.